The consept of Jinn in Islam and Christian orthodox (Comparative study of the books of abbot N and Malik Ibrahim) - Vdovin Ilya Mikhailovich (Program Pascasarjana UIN Sunan Kalijaga, 2015)
st,1/ws.c.1